2023
DOI: 10.3390/nu16010135
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in Adult Patients: A Treatable Metabolic Condition

Domingo González-Lamuño,
Francisco Jesús Arrieta-Blanco,
Elena Dios Fuentes
et al.

Abstract: Hyperhomocysteinemia (HHcy) is recognized as an independent risk factor for various significant medical conditions, yet controversy persists around its assessment and management. The diagnosis of disorders afffecting homocysteine (Hcy) metabolism faces delays due to insufficient awareness of its clinical presentation and unique biochemical characteristics. In cases of arterial or venous thrombotic vascular events, particularly with other comorbidities, it is crucial to consider moderate to severe HHcy. A nutri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Our results indicated that increased Met levels were accompanied by increased serum Hcy levels. It is commonly accepted that elevated Hcy is also associated with various conditions, which may be one of the reasons that high TSAA/Lys ratio induced lower feed intake in our study. Additionally, we also observed that there was a significant interaction between sources and levels of the CBS expression and serum levels of Hcy.…”
Section: Discussionmentioning
confidence: 57%
“…Our results indicated that increased Met levels were accompanied by increased serum Hcy levels. It is commonly accepted that elevated Hcy is also associated with various conditions, which may be one of the reasons that high TSAA/Lys ratio induced lower feed intake in our study. Additionally, we also observed that there was a significant interaction between sources and levels of the CBS expression and serum levels of Hcy.…”
Section: Discussionmentioning
confidence: 57%
“…Homocysteine (Hcy) is an intermediate thiol-containing nonproteinogenic amino acid derived from methionine catabolism, which is metabolized via remethylation or trans-sulfuration into cysteine [ 1 ]. Hcy plays a critical role in endothelial dysfunction, atherosclerosis, and thrombosis through various mechanisms, such as inflammation, lipid peroxidation, ferroptosis, and platelet activation [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%